Benchmarking cryo-EM Single Particle Analysis Workflow - Kim, Laura Y.; Rice, William J.; Eng, Edward T.; Kopylov, Mykhailo; Cheng, Anchi; Raczkowski, Ashleigh M.; Jordan, Kelsey D.; Bobe, Daija; Potter, Clinton S.; Carragher, Bridget (Frontiers in Molecular Biosciences, 2018)
Cryo electron microscopy facilities running multiple instruments and serving users with varying skill levels need a robust and reliable method for benchmarking both the hardware and software components of their single particle analysis workflow. The workflow is complex, with many bottlenecks existing at the specimen preparation, data collection and image analysis steps; the samples and grid preparation can be of unpredictable quality, there are many different protocols for microscope and camera settings, and there is a myriad of software programs for analysis that can depend on dozens of settings chosen by the user. For this reason, we believe it is important to benchmark the entire workflow, using a standard sample and standard operating procedures, on a regular basis. This provides confidence that all aspects of the pipeline are capable of producing maps to high resolution. Here we describe benchmarking procedures using a test sample, rabbit muscle aldolase.